2020
DOI: 10.3390/v12101197
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of Pseudo-Nucleus Compartment in P. aeruginosa, Infected with Giant phiKZ Phage

Abstract: The giant phiKZ phage infection induces the appearance of a pseudo-nucleus inside the bacterial cytoplasm. Here, we used RT-PCR, fluorescent in situ hybridization (FISH), electron tomography, and analytical electron microscopy to study the morphology of this unique nucleus-like shell and to demonstrate the distribution of phiKZ and bacterial DNA in infected Pseudomonas aeruginosa cells. The maturation of the pseudo-nucleus was traced in short intervals for 40 min after infection and revealed the continuous spa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 41 publications
4
35
0
Order By: Relevance
“…It also expresses several other systems that the host lacks entirely. During infection, ΦKZ forms a ‘nucleus’ within the host cytoplasm that protects its genome from host endonucleases, and which it traffics with a tubulin cytoskeleton ( 6 , 7 ). This implies intriguing evolutionary parallels to their eukaryotic equivalents, and suggests a possible viral origin for the eukaryotic nucleus and cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%
“…It also expresses several other systems that the host lacks entirely. During infection, ΦKZ forms a ‘nucleus’ within the host cytoplasm that protects its genome from host endonucleases, and which it traffics with a tubulin cytoskeleton ( 6 , 7 ). This implies intriguing evolutionary parallels to their eukaryotic equivalents, and suggests a possible viral origin for the eukaryotic nucleus and cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was found that that phage phiKZ encodes a proteinaceous shell that assembles a nucleus-like structure that compartmentalizes proteins and DNA during viral infection [47,48] and in this way segregates its DNA from the immunity mechanisms of its bacterial host (two subtypes of CRISPR-Cas3, Cas9, Cas12a and the restriction enzymes HsdRMS and EcoRI) [49]. Phage-encoded tubulin-like protein is supposed to play a role in positioning this structure in the cell [45,50] The DNA polymerase was finally found in phiKZ-like phages genomes by way of very thorough bioinformatical analysis and appeared to represent an unexpectedly highly divergent newly discovered branch of the B-family DNA polymerases [51][52][53].…”
Section: Bacteriophage Phikz Genomementioning
confidence: 99%
“…Giant phiKZ-like bacteriophages belong to myoviruses, which include Pseudomonas aeruginosa phiKZ, EL, OBP, and Pseudomonas chlororaphis 201phi2-1 that are found to have circular genomes. 44,45 These genomes are packaged inside the capsid through a head-full packaging mechanism ensuring that the entire interior space of the viral protein head is filled with DNA in the course of the DNA packaging. After genome sequencing of the giant phages, it is concluded that their genomes encode structural proteins of capsid and tail, RNA polymerases, 26,46 chaperonins, 45,47 and inner body proteins.…”
Section: Genetic Characterizationmentioning
confidence: 99%
“…44,45 These genomes are packaged inside the capsid through a head-full packaging mechanism ensuring that the entire interior space of the viral protein head is filled with DNA in the course of the DNA packaging. After genome sequencing of the giant phages, it is concluded that their genomes encode structural proteins of capsid and tail, RNA polymerases, 26,46 chaperonins, 45,47 and inner body proteins. 48 Virus inner body possessed an internal proteinaceous structure, specific for jumbo phages.…”
Section: Genetic Characterizationmentioning
confidence: 99%